2012
DOI: 10.5216/rpt.v41i4.21706
|View full text |Cite
|
Sign up to set email alerts
|

Alterações Do Hemograma No Diagnóstico De Dengue: Um Estudo De 1.269 Casos Na Cidade De Uberaba, Minas Gerais

Abstract: Introdução: O dengue é uma doença infecciosa frequente no Brasil e, particularmente, na cidade de Uberaba, Minas Gerais. A doença se manifesta em um amplo espectro de sintomas que levam a alterações nos parâmetros do hemograma. Em nosso trabalho, procuramos estudar a frequência de cada uma das alterações nas séries vermelha, branca e plaquetária em pacientes acometidos pelo dengue em Uberaba-MG, comparando os biênios de 2005-2006 e 2009-2010. Métodos: Foram analisados hemogramas de pacientes atendidos em labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 9 publications
(12 reference statements)
1
3
0
2
Order By: Relevance
“…A slight alteration was detected in males. Increase occurred in only two cases (0.5%) and corroborates a study in the state of Minas Gerais, Brazil, in which only four (0.38%) out of 1,061 patients assessed in 2005-2006 experienced a rise in hematocrits (OLIVEIRA et al, 2012).…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…A slight alteration was detected in males. Increase occurred in only two cases (0.5%) and corroborates a study in the state of Minas Gerais, Brazil, in which only four (0.38%) out of 1,061 patients assessed in 2005-2006 experienced a rise in hematocrits (OLIVEIRA et al, 2012).…”
Section: Discussionsupporting
confidence: 65%
“…Current assay demonstrates that hepatic enzymes mostly changed in females. One study showed higher rates of transaminases in males than in females although it was underscored that AST increase may be associated with alcohol consumption mostly associated to males (OLIVEIRA et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…NAKAO et al, (1989) demonstrou que o vírus da dengue se propaga nos progenitores hematopoiéticos que estão na medula óssea, o que altera a diferenciação e consequentemente a capacidade proliferativa. O vírus da dengue do tipo 2, parece ainda inibir a diferenciação de células CD34 positivas induzindo a apoptose os progenitores hematopoiéticos (NAKAO; LAI; YOUNG, 1989) (Figura 2).…”
Section: Seu Uso Portanto é Desaconselhado(martins; Setúbal; Castiñeunclassified